Occupational safety and health and employability : programmes, practices and experiences (Luxembourg, 2001)
"This report gives an overview of the different types of initiatives in the Member States that aim to increase the employability of workers by using interventions deriving from the field of Occupational Safety and Health. Twenty-six case studies from 13 Member States highlight the potential role of Occupational Safety and Health to improve the employability of workers, including prevention programmes and programmes aimed at (re)integrating specific groups at work. "